Audit of patients attending the pain clinic of Shaheed Suhrawardy Medical College Hospital in Bangladesh during the period 2022-2023 (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Pain is an unavoidable part of life. More than 1.5 billion people worldwide live with chronic pain and the prevalence rate is about 11.6%. Pain clinics are healthcare facilities that provide standard services to help people manage their pain and regain control of their lives. The objective of this study was to analyze the chronic pain patients of the pain clinic of Shaheed Suhrawardy Medical College Hospital between 2022 and 2023.Methods: This was a retrospective observational study conducted in the pain clinic of Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh. Patients with persistent pain for more than 3 months attending the pain clinic between 1 January 2022 and 31 December 2023 were included. Sociodemographic variables, pain characteristics, pain intensity at the first visit, pain duration, and treatments were extracted from the records.Results: After reviewing the clinical records, 934 patients were selected for this study. The mean age of the patients was 41.62 ± 10.87 years. The persistent pain duration was 10.52 ± 2.25 months and 542 (58%) experienced moderate pain measured by visual analogue scale (VAS). Most of the patients suffered from chronic musculoskeletal pain 456 (49%) followed by chronic neuropathic pain 196 (21%) and chronic post-traumatic pain 159 (17%). A large proportion complained of localized pain 719 (77%) and the lower back was the most prevalent site 446 (48%). A great number of patients 662 (71%) were treated conservatively rather than interventions 272 (29%) to manage their pain. The most common type of intervention was epidural injection (30%) followed by intra-articular injection (21%) and nerve blocks (15%).Conclusion: This research sheds light on the role of pain clinics in crafting tailored pain management strategies. This study's findings give insight into chronic pain patients and pain management practices who attended the pain clinic.J Shaheed Suhrawardy Med Coll 2023; 15(2): 6-11